2021
DOI: 10.21608/svuijas.2021.85028.1125
|View full text |Cite
|
Sign up to set email alerts
|

Impact of certain weather factors and plant age on the population density of Aphis craccivora (Koch) on faba bean plants.

Abstract: Field studies were done on faba bean plants at the El-Mattana Agricultural Research Station in Luxor Governorate, Egypt, throughout two successive growing seasons (2019/20 and 2020/21) to investigate the seasonal activity of the cowpea aphid, Aphis craccivora (Koch) (Hemiptera: Aphididae) (Giza 843 cultivar). As well, estimate the effects of some climatic conditions and plant ages on the seasonal abundance of A. craccivora. In this study, two insect expressions were used, i.e., insect numbers and incidence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
(14 reference statements)
0
5
0
Order By: Relevance
“…In determining insect population dynamics on a host plant, ambient temperature, natural enemies of insects and host plant status are key factors. In addition, Mohamed, et al (2021) the Results indicated that A. craccivora infested faba bean plants from 21 st November 2019 to 12 th March 2020 during the first growing season and from 22 nd November 2020 to 13 th March 2021 through the second one. According to the findings, the combined impacts of environmental conditions and plant ages can explain changes in A. craccivora population density.…”
Section: Discussionmentioning
confidence: 90%
“…In determining insect population dynamics on a host plant, ambient temperature, natural enemies of insects and host plant status are key factors. In addition, Mohamed, et al (2021) the Results indicated that A. craccivora infested faba bean plants from 21 st November 2019 to 12 th March 2020 during the first growing season and from 22 nd November 2020 to 13 th March 2021 through the second one. According to the findings, the combined impacts of environmental conditions and plant ages can explain changes in A. craccivora population density.…”
Section: Discussionmentioning
confidence: 90%
“…According to Bakry et al (2020) and Mohamed et al (2021), the weekly variation rate within FAW population was estimated as follows (Formula 2): ( )…”
Section: Estimate the Weekly Variation Rate In Faw Populationmentioning
confidence: 99%
“…A third-degree polynomial equation was established to represent these relationships (i.e., age, age 2 , and age 3 according to the sampling dates). The following formula was applied: Y = a ± b 1 X 4 ± b 2 X 4 2 ± b 3 X 4 3 (Bakry et al, 2020;Mohamed et al, 2021). According to Fisher (1950), data were statistically analyzed, by using different models of correlation and regression, to find out the relationships between the main weather factors and plant ages (independent variables), the numbers of egg masses, the larval population density, and percentages of damaged plants (as dependent variables).…”
Section: Simultaneous Effects Of Both Climatic Factors and Plant Ages...mentioning
confidence: 99%
“…temperature and average temperature r= -0.61, and -0.57 for the 2010 season, whereas maximum temperature, minimum, and average temperature were negatively insignificant correlations in the 2011 season. Mohamed et al (2021) reported that the partial regression values for the effect of daily mean max. the temperature on the A. craccivora population were a significant positive relation (P. reg.…”
Section: The Second Season 2021-2022mentioning
confidence: 99%